A Sociocultural Examination of Religiosity's Role in Coupon Proneness - Ding, William; Sprott, David; Joireman, Jeff (Psychology and Marketing, 2026)
Keywords: Consumer behaviour; Coupon; Face (sociological concept); Religiosity; Revenue; Sociocultural evolution; Survey data collection; benevolent inference; coupon proneness; dept.mrk; mixed method; religiosity; sociocultural variables

Conspicuous gifting: When and why women (do not) appreciate men's romantic luxury gifts - Ding, William; Pandelaere, Mario; Slabbinck, Hendrik; Sprott, David E. (Journal of Experimental Social Psychology, 2020)
While research suggests that conspicuously displaying luxury goods can help men signal desirable qualities such as high earning capacity and social status, little is known about how women evaluate and interpret luxury items given as romantic gifts by men. The current research explores this under-researched question and reveals that women do not always react favorably to luxury gifts. Instead, women are wary that accepting luxury gifts may lead to relationship power imbalance, which prompts less favorable reactions to such gifts. We also test the competing explanation of relationship commitment and find that signaling commitment does not emerge until a relationship becomes more established. Furthermore, individual differences in power distance belief (PDB) are explored to test our theoretical explanation with results indicating that women low in PDB are more likely to have concerns about power imbalance. Together, these findings highlight the unique role of luxury gifts in romantic relationships and thereby advance our understanding of when and why men's romantic luxury gifts will be appreciated by women. More generally, our findings provide nuanced insights into the power dynamics between men and women and the progression of a romantic relationship. Implications for luxury consumption and gender stereotypes are discussed.
Keywords: Conspicuous consumption; Gift giving; Power imbalance; Relationship norm; dept.mrk; peer-reviewed

Political Polarization: Challenges, Opportunities, and Hope for Consumer Welfare, Marketers, and Public Policy - Weber, T.J.; Hydock, Chris; Ding, William; Gardner, Meryl; Jacob, Pradeep; Mandel, Naomi; Sprott, David E.; Van Steenburg, Eric (Journal of Public Policy & Marketing, 2021)
Political polarization is a marked political division in the population, characterized by multiple manifestations. The authors argue that it can affect consumer psychology, which in turn influences marketers, policy makers, and consumer welfare. The present work introduces the construct of political polarization to the marketing literature and shows how it serves as a novel challenge for various marketing stakeholders. For consumers, the authors propose that political polarization increases the salience of political identities, alters inter- and intragroup dynamics, and amplifies cognitive biases. These effects negatively affect consumer welfare, including financial welfare, relationships, mental and physical health, and societal interests. For marketers, polarization introduces a challenge to both be more sociopolitically engaged while also navigating competing political interests. Polarization also creates new opportunities and challenges for segmentation, targeting, loyalty, and product offerings. For policy makers, political polarization creates policy gaps, impedes the implementation of policy, and obstructs governance. Building from these insights, the authors consider the drawbacks and overlooked benefits of political polarization, potential remedies, and directions for future research.
Keywords: dept.mrk; peer-reviewed